ENHANCING EMPLOYEES PERFORMANCE THROUGH A WORK ETHIC WITH ISLAMIC SPIRITUAL LEADERSHIP BASED, HUMAN RELATION, ORGANIZATIONAL SUPPORT, WORKPLACE SPIRITUALITY, AND ORGANIZATIONAL COMMITMENT - Elviera Rosa Pangestika (UNISSULA, 2018)
This study aims to test and analyze employee performance improvement through work ethos with the influence of spiritual leadership of Islam, human relations, organizational support, workplace spirituality,organizational commitment. Population in this research is employees of Islamic Hospital Nahdlatul Ulama Demak which amounted to 68 people with respondent retrieval through purposive sampling techniquewith census method. Analyzer used is path analysis. From the result of data test by using SPSS, it is found that spiritual leadership of Islam, human relation, organizational support, workplace spirituality,organizational commitment have positive and significant effect to work ethic, meaning if spiritual leadership of Islam, human relation, organizational support, workplace spirituality, then it will increase the work ethic. Spiritual leadership and organizational commitment have a positive and significant impact on employee performance, meaning that if spiritual leadership and organizational commitment increase then it will improve employee performance. The work ethic variables are evident as intervening variables with the mediation of spiritual leadership of Islam, human relations, organizational support, workplace spirituality, organizational commitment to employee performance.Keywords: Spiritual leadership of Islam, human relations, organizational support, workplace spirituality, organizational commitment, work ethic, employee performance.